Mix de medios como estrategia clave para la promoción de productos lácteos. - Villavicencio, Maria Fernanda; Jaramillo González, Mayra Lucia; Gallegos Calderón, Evelyn Katiuska; Sánchez Saritama, Luis Joel (My University, 2021)
To analyze the consumption habits of housewives of the Pasaje canton, in relation to digital and traditional media that determine the effectiveness of a promotional campaign for dairy products.Stratified probability sampling, housewives aged 15 to 44 years.Results: 48.0% of respondents use both means, 30.5%; digital media; 21% traditional media and 0.5% do not use media.An efficient media mix to promote dairy products needs to apply strategies in digital and traditional media at the national and local level.
Analizar los hábitos de consumo de amas de casa del cantón Pasaje, en relación a los medios digitales y tradicionales que determinen la efectividad de una campaña promocional para productos lácteos. Muestreo probabilístico estratificado, amas de casa de 15 a 44 años. El 48,0 % de encuestadas utilizan ambos medios, el 30,5%; medios digitales; el 21% medios tradicionales y el 0,5% no utilizan medios. Un eficiente mix de medios para promocionar productos lácteos, necesita aplicar estrategias en medios digital es y tradicionales a nivel nacional y local
Keywords: MIX DE MEDIOS; MEDIOS DIGITALES; MEDIOS TRADICIONALES; AMAS DE CASA